Implementation of Multicultural Education in Learning at State Primary School 01 Alitupu - Kasmiati, Kasmiati; Palaguna, Jumadil; Hamka, Hamka; Kahar, M. Iksan; Rahmayanti, Siti (LP. Ma'arif Janggan Magetan, 2024)
Multicultural education in learning has an important role in building mutual respect and respect for differences in the lives of students at school. One of the schools that implements multicultural education in learning is SD N 01 Alitupu. For this reason, this research aims to discover and explain the implementation of multicultural education in learning held at SD N 01 Alitupu. The research method used is a case study, namely examining and analyzing the success of multicultural education in learning implemented by SD N 01 Alitupu. Data collection techniques are carried out using interviews, observation, and documentation where the data results are examined through data reduction techniques, data presentation, and data verification. The results of the research are the substantive foundations used by schools in implementing multicultural education, namely religion and Pancasila which are integrated into learning in each subject. The learning process is carried out based on conveying knowledge and multicultural values ​​originating from religion and Pancasila.